Open Channel Overflow Diversion Structures with Side-Weirs - Mitri, Sabri Hani (My University, 1981)
Combined sewer systems are designed to bypass excess flows directly to the receiving water during rainstorm events. This is commonly achieved by means of diversion structures incorporating side spillways, oblique weirs or orifices.
The simulation of diversion devices by the EXTRAN Block of the Stormwater Management Model is examined. Results for the weir algorithm were not satisfactory. Therefore, a new procedure is written to compute the overflow and the water surface profile along the side weir. The hydraulics of flow over side weirs is reviewed in detail. The momentum approach is used in computing the water surface profile. The coefficient of discharge is estimated from a newly proposed relationship. A method for predicting the formation of a hydraulic jump along the weir section is derived from the momentum balance between the upstream and downstream side of the jump.
A computer program called OVRFLO3 is developed to compute the overflow and the water surface profile. Validation tests show good agreement with observations.
Finally, OVRFLO3 is adjusted to fit the SWMM package. The new Block is called SIDWEIR.
Keywords: Civil Engineering; Civil Engineering